Seasonal microclimatic variation in a succession gradient of low thorn forest in Northeastern Mexico - Sánchez-Reyes, Uriel Jeshua (2019)
Global increase in land cover change and deforestation bring about fragmentation of a high proportion of native vegetation areas. Microclimate is among the first modified factors after vegetation loss, effects of such disturbances are critical for species performance. However, both secondary succession and seasonality provoke further modifications in abiotic environment after disturbances. Although microclimate patterns during succession are well studied for several ecosystems, they are practically unknown for low thorn forests. In Northern Mexico, this is an endangered ecosystem characterized by harboring a high percentage of endemics. Measurement of microclimatic factors is crucial for understanding possible consequences of post-disturbance time on species inhabiting this ecosystem. This work aimed to assess seasonal variation of microclimatic patterns in a succession gradient of four categories (conserved areas, 31, 17 and four years of succession). The study area was delimited using Landsat satellite images (1973, 1986, 2000, 2005, and 2013) in a fragment of low thorn forest in Northeastern Mexico. For microclimate characterization we studied wind speed, temperature, relative humidity, heat index, dew point, and evapotranspiration. Variables were measured monthly on eight plots, in each of the four successional categories, during two different seasons: wet (May through October 2016) and dry season (November 2016 through April 2017). A multivariate discriminant function analysis showed that microclimate differs among successional stages. In the wet season, early succession areas were characterized by higher values of heat index and wind speed, contrary to conserved areas. In the dry season, successional differences were attributed to wind speed and relative humidity. Moreover, microclimate differences between categories and importance of variables measured were both higher only during the dry season. Our results show that seasonality influences greatly microclimatic patterns during secondary succession. In addition, each one of the successional categories exhibited unique microclimatic conditions. Remarkably, four, 17, and even 31 years succession categories differed from conserved areas. This work provides evidence on the great relevance of seasonality and microclimate for studying secondary succession. It is suggested to take both factors into consideration when implementing conservation programs concerning endangered habitats such as low thorn forests. As an ecosystem poorly studied, microclimate characterization provided herein, shall help to a better understanding and management of these areas.